2021
DOI: 10.1101/2021.01.08.426011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiome features are associated with sepsis onset and outcomes

Abstract: BackgroundEpidemiologic studies have linked antibiotic exposure to subsequent sepsis, suggesting that microbiome disruption may be in the causal pathway and an independent risk factor. This study tests whether variation in the gut microbiota associates with risk of sepsis onset and its outcomes.MethodsUsing a validated surveillance definition, patients with an archived rectal swab from intensive care and hematology units were screened for sepsis. After confirmation by chart review, cases were matched to contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our group and others have shown that gut microbiota undergo rapid and temporally dependent changes in hospitalized patients [15,75,76]; therefore, the finding that temporally discordant samples show large differences in observed microbiota is unsurprising. This study adds to the growing body of literature demonstrating the clinical utility of rectal swab specimens for the characterization of gut microbiota, and we replicate findings that admission rectal swabs are predictive of infection and outcomes in ICU patients [64,77].…”
Section: Discussionsupporting
confidence: 66%
“…Our group and others have shown that gut microbiota undergo rapid and temporally dependent changes in hospitalized patients [15,75,76]; therefore, the finding that temporally discordant samples show large differences in observed microbiota is unsurprising. This study adds to the growing body of literature demonstrating the clinical utility of rectal swab specimens for the characterization of gut microbiota, and we replicate findings that admission rectal swabs are predictive of infection and outcomes in ICU patients [64,77].…”
Section: Discussionsupporting
confidence: 66%
“…However, more subtle changes occur that have long-term consequences. Recent studies have shown that decreased microbiota diversity with increased abundance of the genus Enterococcus is observed in critically ill patients and is associated with a higher risk of sepsis, which may give credence to this line of investigation [35][36][37][38][39]. In a study involving 24 long-stay ICU patients, approximately two-thirds of patients were observed to have a loss of microbial diversity based on 16S rRNA gene sequencing of bacteria in the stool.…”
Section: The Microbiome In Sepsis 21 Background and Associationsmentioning
confidence: 94%
“…Furthermore, three-quarters of patients were observed to have increased abundance of pathogens Enterococcus faecium, Klebsiella pneumoniae, Enterobacter cloacae, and E. coli [38]. More specific to sepsis, a study on stool samples of 103 sepsis patients compared to matched controls on intensive care and hematology units were observed to have a higher abundance of Enterococcus based on 23S rRNA gene sequencing (to calculate total abundance) as well [39]. The differential overexpression of this taxa supports the hypothesis that components of the host microbiota can mediate or elevate sepsis risk.…”
Section: The Microbiome In Sepsis 21 Background and Associationsmentioning
confidence: 99%
“…Loss of diversity and imbalance in composition of the microbiota, termed dysbiosis, is clearly described but associations with mortality risks are not. Dysbiosis is likely correlated with illness severity and has been linked to increased mortality in critically ill patients including sepsis 54,55 , in patients undergoing allogeneic hematopoietic-cell transplantation 56 , in hospitalized patients with cirrhosis 57 among others. A marked insult on the microbiome is likely when children are hospitalized and exposed to nosocomial microorganisms, and to selection pressure from antimicrobials, resulting in acquisition of antimicrobial resistance genes.…”
Section: The Gut Microbiotamentioning
confidence: 99%